2013
DOI: 10.1007/s10495-013-0835-5
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species-mediated activation of the Akt/ASK1/p38 signaling cascade and p21Cip1 downregulation are required for shikonin-induced apoptosis

Abstract: Shikonin derivatives exert powerful cytotoxic effects, induce apoptosis and escape multidrug resistance in cancer. However, the diverse mechanisms underlying their anticancer activities are not completely understood. Here, we demonstrated that shikonin-induced apoptosis is caused by reactive oxygen species (ROS)-mediated activation of Akt/ASK1/p38 mitogen-activated protein kinase (MAPK) and downregulation of p21(Cip1). In the presence of shikonin, inactivation of Akt caused apoptosis signal-regulating kinase 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 48 publications
0
43
0
2
Order By: Relevance
“…In the human gastric cancer cell line AGS, shikonin induces apoptosis through the inhibition of PI3K/Akt and ERK activities and the augmentation of p38 activity [45]. In the cervical cancer cell line HeLa, the colon cancer cell line Hct116, the lung cancer cell line A549, and the hepatocellular carcinoma cell lines Hep3B, BEL7402, and Huh7, shikonin increases ROS production, inactivates PI3K/Akt, and subsequently promotes apoptosis [46,47]. Shikonin promotes glucose transporter 4 translocation into the plasma membrane via the PI3K/Akt pathway [48].…”
Section: Discussionmentioning
confidence: 99%
“…In the human gastric cancer cell line AGS, shikonin induces apoptosis through the inhibition of PI3K/Akt and ERK activities and the augmentation of p38 activity [45]. In the cervical cancer cell line HeLa, the colon cancer cell line Hct116, the lung cancer cell line A549, and the hepatocellular carcinoma cell lines Hep3B, BEL7402, and Huh7, shikonin increases ROS production, inactivates PI3K/Akt, and subsequently promotes apoptosis [46,47]. Shikonin promotes glucose transporter 4 translocation into the plasma membrane via the PI3K/Akt pathway [48].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of angiogenesis and migration by fenofibrate was related to the decreased Akt [43,44]. Akt activation might either inhibit apoptosis by phosphorylation of Bad [45], or lead to cell cycle arrest by down-regulation of p27/Kip1 [46] and p21 [47]. Inhibition of PI3K activity, leading to inhibition of Akt, induced G0/G1 phase cell cycle arrest accompanied by the decreased expressions of Cyclin D1 and Cdk4 [48].…”
Section: Discussionmentioning
confidence: 99%
“…Shikonin is also reported to influence apoptosis to some extent (Chang et al 2010;Liu et al 2014) and can regulate the AKT/ASK1/p38 pathway or reactive oxygen species levels to induce apoptosis (Ahn et al 2013;Duan et al 2014;Lee et al 2014). Our study revealed that a low concentration of shikonin has no apparent effect on apoptosis, but in the presence of TNF-␣, shikonin induces apoptosis in a concentrationdependent manner, promotes the activation of caspase-3 and (G, H) The expression levels of cyclin D1 and cyclin E were measured by Western blot after treatment with different concentrations of shikonin and TNF-␣.…”
Section: Discussionmentioning
confidence: 99%